2005
DOI: 10.1007/s10815-005-1501-9
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of the Effects of Cryopreservation in Bovine Ovarian Tissue

Abstract: The aim of this study was to show the effects of freezing and thawing in bovine ovarian tissue by histological analysis. Ten cortical slices (2-4 mm in diameter) were obtained from each ovary by tru-cut biopsy and randomly divided into two groups: five fragments were immediately processed as a fresh tissue control group, while the remaining 5 fragments were slowly frozen using DMSO plus sucrose as cryoprotectors, then stored for two weeks and quickly thawed. Histological examination of all cryopreserved ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
2
3
1
2
Order By: Relevance
“…These results are consistent with the results of a comparative study on fresh and frozen-thawed ovarian tissue using DMSO or 1,2-propanediol (PROH) as cryoprotectants in human (34,35) and in bovine ovarian tissue (36). The complementary results of the study show that the freezing combined with thawing induce an increase in the detection of apoptotic cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with the results of a comparative study on fresh and frozen-thawed ovarian tissue using DMSO or 1,2-propanediol (PROH) as cryoprotectants in human (34,35) and in bovine ovarian tissue (36). The complementary results of the study show that the freezing combined with thawing induce an increase in the detection of apoptotic cells.…”
Section: Discussionsupporting
confidence: 87%
“…The complementary results of the study show that the freezing combined with thawing induce an increase in the detection of apoptotic cells. The studies on the sheep did not find more fragmentation of DNA after freezing (36,37), but the interpretation of results and the study model were different from ours. However, results of these investigators regarding the percentage and distribution of morphologic abnormalities showed tissue injury by cryopreservation.…”
Section: Discussioncontrasting
confidence: 63%
“…To our knowledge, we are the first to report on successfully vitrified isolated bovine follicles, in combination with repeated NR viability assessment prior and following cryopreservation and subsequently cultured for a short-term period. In line with earlier work on follicles embedded in cortical tissue strips [56,57], we showed that cryopreservation, as compared with non-cryopreserved follicles, has an overall negative effect on the viability of isolated (bovine) PAFs, as noticed immediately after warming and at 4 days of culture. We have used NR as an indicator or build-in sentinel for easy and routine applicable assessment of PAF's metabolic activity.…”
Section: Discussionsupporting
confidence: 91%
“…Gandolfi et al (2006) compararam duas técnicas de vitrificação com a técnica de congelação lenta usando fragmentos ovarianos de humanos, suínos e bovinos, e concluíram que a vitrificação, independentemente de espécie, classe folicular e técnica, não foi adequada para a preservação de folículos pré-antrais quando comparada com a técnica de congelação lenta. Têm-se obtido excelentes resultados com a congelação lenta de tecido ovariano bovino, em determinados estudos, mais de 70% de preservação da normalidade folicular (Paynter et al, 1999;Lucci et al, 2004;Lamaita et al, 2005;Celestino et al, 2007), levando a assumir que a técnica de congela- Tabela 2. Diâmetro do folículo (mm) e ovócito (mm) e número de células da granulosa (média ± desvio padrão) de folículos primários no T 0 (controle), T I (teste de toxicidade) e T II (vitrificação)* ção lenta é a mais apropriada para criopreservação de tecido ovariano bovino.…”
Section: Resultsunclassified